Ukraine : Request for Stand-by Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Ukraine's Request for Stand-By Arrangement. The 2020 budget is expected to be hit hard, with a sharp decline in revenues and large emergency spending needs to address the crisis. This has created large balance of payments and fiscal financing needs. Sound fiscal and monetary policies since the 2014-2015 crisis have resulted in a sharp reduction in Ukraine's external and internal imbalances. Public debt was put on a downward path, inflation has declined, and international reserves have recovered. The new Stand-By Arrangement will provide an anchor for the authorities' efforts to address the impact of the crisis, while ensuring macroeconomic stability and safeguarding achievements to date. Together with support from the World Bank and the European Union, it will help address large financing needs. The program will focus on safeguarding medium-term fiscal sustainability, preserving central bank independence and the flexible exchange rate, and enhancing financial stability while recovering the costs from bank resolutions. Concerted reform efforts aimed at tackling corruption and strengthening governance will be critical to ensure macroeconomic stability and achieve sustainable and inclusive growth.